The hospital-to-home care transition experience of home care clients: an exploratory study using patient journey mapping - Marianne Saragosa; Sonia Nizzer; Sandra McKay; Kerry Kuluski (BMC, 2023)
Abstract Background Care transitions have a significant impact on patient health outcomes and care experience. However, there is limited research on how clients receiving care in the home care sector experience the hospital-to-home transition. An essential strategy for improving client care and experience is through client engagement efforts. The study's aim was to provide insight into the care transition experiences and perspectives of home care clients and caregivers of those receiving home care who experienced a hospital admission and returned to home care services by thematically and illustratively mapping their collective journey. Methods This study applied a qualitative descriptive exploratory design using a patient journey mapping approach. Home care clients and their caregivers with a recent experience of a hospital discharge back to the community were recruited. A conventional inductive approach to analysis enabled the identification of categories and a collective patient journey map. Follow-up interviews supported the validation of the map. Results Seven participants (five clients and two caregivers) participated in 11 interviews. Participants contributed to the production of a collective journey map and the following four categories and themes: (1) Touchpoints as interactions with the health system; Life is changing; (2) Pain points as barriers in the health system: Sensing nobody is listening and Trying to find a good fit; (3) Facilitators to positive care transitions: Developing relationships and gaining some continuity and Trying to advocate, and (4) Emotional impact: Having only so much emotional capacity. Conclusions The patient journey map enabled a collective illustration of the care transition depicted in touchpoints, pain points, enablers, and feelings experienced by home care recipients and their caregivers. Patient journey mapping offers an opportunity to acknowledge home care clients and their caregivers as critical to quality care delivery across the continuum.